PERAN PEMERINTAH BRASIL DALAM MENANGGULANGI EKSPLOITASI SEKSUALA KOMERSIAL ANAK (ESKA) DALAM EVEN PIALA DUNIA 2014 - Mukarromah "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study describes about the role of the government of Brasil to ward off sexual exploitation in the event of World Cup 2014. The writer wants explain the role taken by the government of Brasil as wisdom maker in overcoming any problems in the country. The purpose is to eclipse the sexual exploitation of the children in the event of World Cup 2014.This study used a qualitative research method. The technique used is to connect theory with data obtained through library reset, the data obtained from books, journals, magazines, newspapers, websites and other sources cracked. The author uses the theory of the role While the level of analysis that I use in this study is the nation-state.As the coordinator of World Cup 2014, Brasil’s social field is changing. The preparation for the big event causes the children are more vulnerable to be exploited. The agent of the child prostitution business takes the advantages of that event. A business will not exist without the supply and demand of the providers and child sexual services users. The role of the government in overcoming child sexual exploitation is by way of creation and implementation of joining programs with international organizations and local NGOs which are concerned about the problem of sexual exploitation of children in a big event such as World Cup 2014.Key word: Brasil’s Government, FIFA World Cup 2014, Role, sexual exploitation of children, Children trafficking.